Dampak ACFTA pada Pola Ekspor Indonesia: Analisis Trade Creation-Diversion Pendekatan Gravity Model - Ilham Febri Budiman; Reno Malika Wicaksono; Zarifa Zahra Rizma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study analyzes the trade creation and trade diversion effects of the ACFTA agreement on the export patterns of Indonesia's primary and manufactured goods. Using the gravity model with panel data from 20 partner countries from 2000-2023, the model was estimated using the Poisson Pseudo-Maximum Likelihood (PPML) technique. The results show that the impact of ACFTA is heterogeneous. The primary sector experienced significant trade creation (a 9.42% export increase) without classic trade diversion; exports to non-member countries even increased. Conversely, the manufacturing sector showed negative trade creation (-5.88%) and significant trade diversion (-14.96%), indicating that Indonesia's manufacturing industry has not been able to compete within the ACFTA bloc and has experienced market diversion. These findings underscore the urgency of enhancing manufacturing competitiveness to optimize the benefits of free trade agreements.